Inﬂuence of a viral complex on yield and chlorophyl content of two varieties of sweet potato. - Buxmann, E. (Universidad Nacional del Litoral, 2022)
Virus diseases are the main constraint of sweet potato yield, the ﬁfth largest food crop. In Argentina, “yellow curling” (EA), a viral complex with seven agents involved, causes notable losses in all the growing regions. The inﬂuence of EA on yield components of Arapey INIA and Beauregard cultivars was analyzed by comparative trials that combined two health conditions and two genotypes. Healthy plants were obtained by thermotherapy and in vitro culture of meristems and the diseased ones, by grafting with EA. There were signiﬁ cant differences between health conditions, in chlorophyll content and losses in yield characters near to 90%. Weight and number of commercial roots were the most affected by EA in both cultivars. This work corroborates the relevance of EA on sweet potato production. Virus free plants and good management practices increase greatly the yields.